2009
DOI: 10.1371/journal.pone.0004764
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ischemic Regions in a Rat Model of Stroke

Abstract: BackgroundInvestigations following stroke first of all require information about the spatio-temporal dimension of the ischemic core as well as of perilesional and remote affected tissue. Here we systematically evaluated regions differently impaired by focal ischemia.Methodology/Principal FindingsWistar rats underwent a transient 30 or 120 min suture-occlusion of the middle cerebral artery (MCAO) followed by various reperfusion times (2 h, 1 d, 7 d, 30 d) or a permanent MCAO (1 d survival). Brains were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(175 citation statements)
references
References 59 publications
9
157
0
3
Order By: Relevance
“…Since data from postmortem histology 2,9 are still the most reliable translational research method in identifying corepenumbra, we compared our MRI-based HRS with IHC results (Figure 3). Previous reports have shown that markers associated with cellular stress or structural demise (apoptosis-related) can estimate penumbral locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since data from postmortem histology 2,9 are still the most reliable translational research method in identifying corepenumbra, we compared our MRI-based HRS with IHC results (Figure 3). Previous reports have shown that markers associated with cellular stress or structural demise (apoptosis-related) can estimate penumbral locations.…”
Section: Discussionmentioning
confidence: 99%
“…2 In animal models, recent studies have used microtubule-associated protein 2 (MAP2) and neuronal nuclei (NeuN) as immunohistochemical (IHC) markers of viable neurons, heat-shock proteins (HSPs) as markers for activated astrocytes to delineate the penumbra, and glial fibrillary acidic protein (GFAP) as a marker of glial cell activity and structural integrity. 2,9,10 In clinical studies, while DPM has been used to identify salvageable from nonsalvageable tissues, [11][12][13] recent publications have shown that simple volumetric DPM is misleading and emphasizes the need for coregistration between DWI and perfusion-weighted imaging (PWI) which is challenging, particularly in neonates where PWI data are noisy due to increased brain water content. 14 To provide an alternative strategy that might be applicable to neonatal HII, we have shown that a computational approach to MRI analysis, Hierarchical Region Splitting (HRS), can reliably detect and quantify HII lesion volumes from T2 maps that correlate with manually derived measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Another limiting factor of TTC staining is the narrow time window. Although in the case of severe ischemia, TTC staining has repeatedly been described to delineate infarcts as early as 2 to 3 hours after reperfusion (Liszczak et al, 1984;Popp et al, 2009), reliable detection after milder ischemia requires B24 hours (Popp et al, 2009). However, because infiltrating inflammatory cells harbor intact mitochondria, TTC should not be used for time points beyond 24 hours (Liszczak et al, 1984).…”
Section: Light Microscopy and Macroscopymentioning
confidence: 99%
“…The 2,3,5-triphenyltetrazolium chloride method rests on the functioning of mitochondrial enzymes (Liszczak et al, 1984) and has been used by several groups to mark cerebral infarct area (Bose et al, 1988;Park et al, 1988;Hatfield et al, 1991;Goldlust et al, 1996;Kuroiwa et al, 2009;Popp et al, 2009). An obvious advantage of this method is its easy applicability, suitability for infarct volume evaluation and the immediate availability of results (Bederson et al, 1986;Mathews et al, 2000;Türeyen et al, 2004;Popp et al, 2009). Evidence shows that only a sustained ischemia can result in an early (i.e., 4 h after ischemia onset) reliable TTC stain (Popp et al, 2009), agreement with the fact that irreversible injury to mitochondria in brain cells may not occur until after a long period of ischemia (Rehncrona et al, 1979).…”
Section: Ttc Stainingmentioning
confidence: 99%